Comparative Study Of The Effects Of Solidification Rate On The Cast Microstructures Of Aluminum Alloys 6016 And 6009 - P. N. Anyalebechi (The Minerals, Metals and Materials Society, 2006)
The effects of solidification rate on the cast microstructures of aluminum alloys 6009 and 6016 have been investigated with directionally cooled laboratory-size ingots, at 0.2-10.1 K/s and 0.4- 23.1 K/s, respectively. These ranges of solidification rate are within those observed in commercial-size ingots. In both alloys, the average dendrite cell size and second phase particle size decreased with increase in average solidification rate and with a decrease in average local solidification time. However, at comparable solidification rates, the dendrite cells and second phase particles are finer in the shorter freezing range alloy 6009 than in the longer freezing range alloy 6016. This is provisionally attributed to the earlier formation of second phase intermetallics at higher temperatures during solidification and to the formation of greater amount of the relatively coarse plate-like ß -phase (Al9Fe2Si4) phases in alloy 6016. In general, in both alloys, the types and relative amounts of the second phase particles in both alloys are independent of solidification rate.